2022
DOI: 10.1111/1750-3841.16297
|View full text |Cite
|
Sign up to set email alerts
|

Onion (Allium cepa L.) peel: A review on the extraction of bioactive compounds, its antioxidant potential, and its application as a functional food ingredient

Abstract: Functional food development is rapidly increasing as a result of consumer consciousness concerning healthy and nutritious foods. In turn, research exploring novel ingredients for formulating functional foods has been accelerated.Onion peel or skin is a byproduct obtained from onion processing that contains abundant phytochemicals, contributing to its antioxidant potential. The main focus of this review is to highlight different extraction techniques (both conventional and nonconventional) that can be implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…TPCs of red, white, and yellow onion extracts produced by methanol were 132 mg GAE/mL, 112 mg GAE/mL, and 120 mg GAE/mL, respectively [ 23 ]. OS was rich in quercetin, phenolics, and flavonoids, and these compounds have been reported with high antioxidant capacity [ 24 ]. Our result showed that the TPC in OS extract was lower than that in ethanol extract from OS [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…TPCs of red, white, and yellow onion extracts produced by methanol were 132 mg GAE/mL, 112 mg GAE/mL, and 120 mg GAE/mL, respectively [ 23 ]. OS was rich in quercetin, phenolics, and flavonoids, and these compounds have been reported with high antioxidant capacity [ 24 ]. Our result showed that the TPC in OS extract was lower than that in ethanol extract from OS [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with YS, BS exhibits better antioxidant, anti‐obesity and hypolipidemic, anti‐inflammatory, and anti‐cancer effects, especially antioxidant effects mainly owing to its abundant anthocyanins. In this review, we specifically focused on the comparative health benefits of BS and YS, in contrast to previous reviews that focused solely on BS (Bhartiya et al., 2020; Ganesan & Xu, 2017; M. Kumar, Barbhai, Hasan, Dhumal, et al., 2022; M. Kumar, Barbhai, Hasan, Punia, et al., 2022; M. Kumar et al., 2023; Shabir et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Bran, including cereal bran (i.e., rice, wheat, oat), millet bran of both major (jowar, pearl-, finger-millet bran) and minor millet (barnyard-, foxtail-, little-, kodo-, proso-millet bran) are also reported to be a rich source of fiber, antioxidants, phytochemicals and minerals by several investigations documenting their nutritional richness (13)(14)(15)(16)(17)(18)(19). Vegetable and fruit wastes also have ample quantity of fiber, vitamins, minerals and phytochemicals thereby exhibiting healthpromoting abilities (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%